Pengembangan program pelatihan edukator tuberkulosis paru - R Totong Iskandar; Enie Novieastari; Satinah Satinah (Holistik Jurnal Kesehatan, 2021)
The training and development of nursing educators in management of pulmonary tuberculosis Background: The quality of education in patients is a key element in the quality of health promotion in hospitals. The phenomenon that occurs in the pulmonary clinic is the provision of very minimal education and there is no TB educator team.Purpose: To increase the competence of nurses as educators in the pulmonary clinic by carrying out TB educator training.Method: The action research, identification of problems with structured interview techniques, observation, and filling out questionnaires to the district head and 2 persons. Analysis of the problem is done with the fish bone method, solving the problem using the planing of action method.Results: As a condition of completeness of training instruments, curriculum structure and activity descriptions and modules containing training material have been made. From the results of this training a TB educator team will be formed at RS X.Conclusion: The manifestation of the responsibility of the nursing manager in improving the quality of nursing human resources in order to increase the competence of nurses as tb educators in health promotion and prevention of increasing numbers of patients with pulmonary TB in the hospital by compiling the curriculum structure and basic tb educator training modules.Keywords: The training; Development; Nursing educators; Management; Pulmonary tuberculosisPendahuluan: Kualitas edukasi pada pasien menjadi elemen kunci mutu promosi kesehatan di rumah sakit. Fenomena yang terjadi di poliklinik paru ialah pemberian edukasi yang sangat minim dan belum ada tim edukator TB.Tujuan: Untuk meningkatkan kompetensi perawat sebagai edukator di poliklinik paru dengan melaksanakan pelatihan edukator TB.Metode: Metode yang digunakan dengan penelitian tindakan, identifikasi masalah dengan teknik wawancara terstruktur, observasi, dan pengisian kuesioner kepada kabidyankep dan 2 orang kasie. Analisis masalah dilakukan dengan metode fish bone, pemecahan masalah menggunakan metode planing of action.Hasil: Sebagai syarat kelengkapan instrumen pelatihan telah dibuat struktur kurikulum dan deskripsi kegiatan serta modul yang berisi materi pelatihan. Dari hasil pelatihan ini akan dibentuk tim edukator TB RS X.Simpulan: Wujud tanggung jawab manajer keperawatan dalam peningkatan kualitas SDM keperawatan guna meningkatkan kompetensi perawat sebagai edukator TB dalam promosi kesehatan dan pencegahan peningkatan angka penderita TB Paru di rumah sakit yakni dengan menyusun struktur kurikulum dan modul pelatihan edukator TB dasar.